The pass/fail grading system at Jordanian universities for online learning courses from students’ perspectives - Al-Sayyed, Rizik; Abu Awwad, Ferial; Itriq, Mariam; Suleiman, Dima; AlSaqqa, Samar; AlSayyed, Ayat (Frontiers in Education, 2023)
This study aimed to investigate the perspectives of Jordanian university students towards the pass/fail grading system (PFGS) that was used during the Corona pandemic. To achieve this goal, a questionnaire was prepared, consisting of 37 items in its final form; divided into four subscales: advantages, drawbacks of (PFGS), the reasons for its use by students, and their attitudes towards it. This questionnaire was applied to a sample of 6,141 male and female students from four Jordanian universities (Al al-Bayt University, Balqa Applied University, The Hashemite University, and The University of Jordan). The results revealed that most students were satisfied with applying the PFGS to all courses. They believed that the PFGS was the best choice for grading due to online exams and full distance learning lectures. The results showed significant differences at α=0.05 in how students evaluated the PFGS (namely its advantages, drawbacks, reasons, and their attitudes toward it) based on participants’ gender, school, and academic level.